SU(3) breaking and annihilation effects in the η and η′ masses - Carvalho, W. S.; Antunes, ACB; DeCastro, A. S. (World Scientific Publ Co Pte Ltd, 1997)
The mass splitting of the pseudoscalar mesons η and η′ is approached by taking into account the SU(3)-flavor symmetry breaking and annihilation effects. An extended version of the Schwinger sum rule and a mixing angle equal to -19.51° are obtained.